An investigation on fracture toughness of the heat‐affected zone in the welded joints of 13% Cr‐4% Ni martensitic stainless steels. Issue 12 (24th August 2021) - Foroozmehr, Fayaz; Bocher, Philippe
Abstract: Fracture behavior of the welded joints of 13% Cr‐4% Ni stainless steels deposited using multipass flux‐cored arc welding process was examined in both as‐welded and heat‐treated conditions, and J Ic tests were performed. A crack starter notch was placed one millimeter far from the fusion line to evaluate the heat‐affected zone (HAZ). Unstable crack propagations toward the weld metal occurred during stable tearing for both as‐welded and heat‐treated HAZ. Only single‐point fracture toughness J u values could be determined before fracture instability. The fracture toughness of the as‐welded HAZ was about 60% lower than that of the substrate steel but get significantly improved by heat‐treatment, reaching a value even slightly higher than that of the substrate steel. The fracture mode of the stable tearing was transformed from a mix of cleavage and dimpled rupture occurring by micro‐void coalescence mechanism for the as‐welded condition to a totally dimpled rupture in the case of the heat‐treated material. Highlights: Fracture toughness J u of the HAZ was measured at the onset of unstable tearing. Heat treatment increased the J u value of the HAZ by a factor of about three. Cleavage rupture was totally disappeared after heat treatment. The weld metal represents the weakest region against crack growth in the welded joint.